Spatiotemporal Detection of Land Cover Dynamics in Forests and Food Sources in Supporting the Nusantara Capital City of Indonesia - Kiswanto; Mardiany; Gunawan, Ike Anggraeni; Nurrachmawati, Annisa; Pramono, Dwi Agung; Widyasasi, Dyah (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
The relocation of Indonesia's capital from Jakarta to Nusantara in East Kalimantan Province has significantly affected land use, particularly in forests and agricultural resources. This study examines the spatiotemporal dynamics of land cover in the forestry and agricultural sectors within Kutai Kartanegara Regency of East Kalimantan Province. The goal is to support the smart forest city concept and enhance food sources within Ibu Kota Nusantara (IKN). Data related to geographical (location) and temporal (time) were analyzed using Geographic Information System (GIS) tools, enabling the mapping, overlaying, and analyzing spatial data over time. The findings show that Kutai Kartanegara has 30% forested areas and 7% agricultural land. There are eight districts with dryland forests, seven with mangrove forests, and fourteen with swamp forests. The study identifies fourteen districts nominated for dryland agriculture, nine for rice fields, and seven for aquaculture. However, forest cover in both drylands and wetlands has been declining annually. Additionally, the study pinpointed potential areas for urban forest development in Tabang District and locations for food production in Anggana, Samboja, and Muara Badak. The findings provide actionable insights for policymakers to optimize land allocation, ensuring sustainable resource management in the evolving ecosystems of the new capital. Keywords: IKN, land cover, food source, forestry, spatiotemporal